Antineoplastic agents exacerbating Charcot Marie Tooth disease: red flags to avoid permanent disability. (4th March 2018) - Ibañez-Juliá, M. J.; Berzero, G.; Reyes-Botero, G.; Maisonobe, T.; Lenglet, T.; Slim, M.; Louis, S.; Balaguer, A.; Sanson, M.; Le Guern, E.; Latour, P.; Ricard, D.; et al.
Abstract: Background: Charcot Marie Tooth (CMT) disease is the most common form of hereditary neuropathy. Due to the high prevalence of mild and undiagnosed forms, patients with CMT disease may be exposed to severe neurotoxicity following the administration of neurotoxic chemotherapies. The aim of this report is to alert oncologists to the potential to precipitate severe irreversible peripheral neuropathies when administering neurotoxic compounds to undiagnosed CMT patients. Material and methods: A retrospective research in the OncoNeuroTox database was performed (2010–2016), searching for patients with the diagnosis of chemotherapy-induced peripheral neuropathy (CIPN) and CMT disease. A comprehensive literature review for previously published cases was performed using the Pubmed and Cochrane databases (1972–2017). Results: Among 428 patients with CIPN, we identified eight patients with concomitant CMT disease. Seven patients out of the eight had no previous diagnosis of CMT disease, although accurate familial history disclosed mild signs of peripheral neuropathy in five cases. Patients themselves had minor stigmata of long-standing peripheral damage. Patients received chemotherapy regimens based on vinca alkaloids, taxanes or a combination of vinca alkaloids and platinum compounds. In two cases, cumulative doses were below or equal to the expected neurotoxic threshold. Following chemotherapy administration, patients developed severe length-dependent sensory-motor deficits. Despite early drug discontinuation, most patients remained severely disabled. Conclusion: A brief checklist to disclose long-standing signs of peripheral neuropathy could be helpful to detect patients with undiagnosed hereditary neuropathies who could be at risk of developing severe irreversible neurotoxicity following the administration of neurotoxic agents.